Modeling the changing work culture using Islamic work values among the Malaysian workforces - Othman, Abdul Kadir; Noranee, Shereen; A Rahman, Mohd Khirzanbadzli; Rochin Demong, Nur Atiqah (Universiti Teknologi Mara Selangor, 2024)
The Malaysian workforce is experiencing a generational shift, with Millennials and Generation Z constituting the majority as Baby Boomers and Generation X retire. This generational disparity often results in differing work attitudes, creating challenges for collaboration and organizational harmony. Islamic values such as Amanah (trust), Itqan (diligence), Ibadah (work as worship), Ihsan (kindness), and respect offer a potential framework to address these challenges. Existing studies explore generational differences in work culture and outcomes but lack an integrative model incorporating Islamic values. This study proposes a framework to moderate generational differences and improve organizational outcomes through these values. By aligning diverse work attitudes with Islamic principles, the model aims to enhance collaboration, commitment, and productivity. The research addresses gaps in understanding generational behaviors in Asian contexts, enriching literature and offering practical guidelines for organizations to leverage workforce diversity effectively and achieve strategic goals.